New Addition of the Genus Onopordum (Compositae) for the flora of Nepal - Sharma, I.; Subedi, M. N. (Journal of Plant Resources, 2008)
Among the flowering plants, Onopordum L. belongs to family Compositae. This genus has not been recorded from Nepal. Recently one species of Onopordum: Onopordum acanthium L. has been collected from Mustasng, Central Nepal. As a new record from the flora of Nepal, he description and distribution of the plants is provided. Keywords: Genus onopordum; Flora Bulletin of the Department of Plant Resources Vol 30, 2008 pp 20-21